"SILVAMP TB LAM" Rapid Urine Tuberculosis Test Predicts Mortality in Patients Hospitalized With Human Immunodeficiency Virus in South Africa. (9th January 2020) - Sossen, Bianca; Broger, Tobias; Kerkhoff, Andrew D; Schutz, Charlotte; Trollip, Andre; Moreau, Emmanuel; Schumacher, Samuel G; Burton, Rosie; Ward, Amy; Wilkinson, Robert J; Barr, David A; Nicol, Mark P; et al.
Abstract: Reducing diagnostic delay is key toward decreasing tuberculosis-associated deaths in people living with human immunodeficiency virus. In tuberculosis patients with retrospective urine testing, the point-of-care Fujifilm SILVAMP TB LAM (FujiLAM) could have rapidly diagnosed tuberculosis in up to 89% who died. In FujiLAM negative patients, the probability of 12-week survival was 86–97%.